2018
DOI: 10.1213/ane.0000000000002851
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Unit Enhanced Recovery Pathway for Patients Undergoing Orthotopic Liver Transplants Recipients: A Prospective, Observational Study

Abstract: An enhanced recovery pathway focused on milestone-based elements of intensive care unit management and predetermined management triggers including hemodynamic goals, fluid therapy, perioperative antibiotics, glycemic control, and standardized transfusion triggers led to reductions in intensive care unit length of stay without an increase in perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…This study demonstrates, for the first time, the feasibility and impact of an OMP on decreasing opioid requirements of LT recipients, without compromising pain control and patient satisfaction. Although previous smaller studies have shown an impact of an ICU ERAS protocol on ICU LOS (3) and a multimodal pain management order set on hospital opioid use, (4) this is the first study to demonstrate the impact of a perioperative pain management protocol on postdischarge opioid utilization patterns. As part of our OMP protocol, we chose to substitute tramadol, which has a much lower MME, for our historical choice of oxycodone.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study demonstrates, for the first time, the feasibility and impact of an OMP on decreasing opioid requirements of LT recipients, without compromising pain control and patient satisfaction. Although previous smaller studies have shown an impact of an ICU ERAS protocol on ICU LOS (3) and a multimodal pain management order set on hospital opioid use, (4) this is the first study to demonstrate the impact of a perioperative pain management protocol on postdischarge opioid utilization patterns. As part of our OMP protocol, we chose to substitute tramadol, which has a much lower MME, for our historical choice of oxycodone.…”
Section: Discussionmentioning
confidence: 72%
“…Although the use of enhanced recovery after surgery (ERAS) protocols has been shown to be effective in decreasing postoperative opioid use in other surgical subspecialties, limited data exist regarding ERAS or other pain management protocols in the LT recipient population. (3,4) At our institution, a novel perioperative opioid minimization protocol (OMP) was implemented for all LT recipients in an effort to decrease perioperative and postdischarge opioid requirements. The objective of this study was to evaluate the feasibility and impact of the OMP on patient pain control and satisfaction.…”
Section: To the Editormentioning
confidence: 99%
“…Among the 14 exposure-based cohort studies, [38][39][40][41][42][43][44][45][46][47][48][49][50][51] nine collected data from the intraoperative period: three compared low CVP with another strategy (one compared two centres using different protocols 38 ; one compared two groups retrospectively classified as to CVP values after reperfusion 39 ; and one compared low CVP with goaldirected therapy in a before-after study) 40 ; one compared stroke volume variation (SVV) goal-directed therapy with high-CVP management 41 ; two from the same centre compared the use of phlebotomies with either unmatched historical controls (before-after study) 42 or contemporary controls 43 ; two compared two retrospectively classified groups (one based on SVV 44 and one based on the volume of fluid received) 45 ; and one compared two groups in a before-after study (practice changed over time toward a more restrictive approach). 46 Three studies collected data for the complete perioperative period (intraoperative and postoperative periods): two before-after studies compared patients receiving a restrictive fluid management (either restrictive goal-directed therapy 47 or a fast-track bundle that included restricting fluid) 48 with unmatched historical controls and one compared two retrospectively classified albumin-treated groups. 49 Two before-after studies collected data during the postoperative period: one compared albumin administration to no administration 50 and one compared patients receiving a goal-directed therapy to unmatched historical controls.…”
Section: Resultsmentioning
confidence: 99%
“…34 The second RCT performed during the postoperative period reported a comparable three-month mortality between three different groups. 36 Among the twelve cohort studies reporting data on mortality, eleven studies did not show any effect [38][39][40][41][42]44,[47][48][49][50]67 and one study reported a lower one-year mortality with the use of intraoperative phlebotomy as part of a restrictive strategy (OR, 0.50; 95% CI, 0.27 to 0.92) 43 (eTable 3a).…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation